The Lost City of the Middle Ages: Arradjan From the by Muslims Conquest Until the Beginning of the XIIth Century - İsmet Burak Batır (Tarih Dergisi)
Established in the Sasanids period, Arradjan is located on the border of Khuzistan and Fars regions. After the Muslim conquest, the first two centuries retained its importance. With the weakening of the authority of the Abbasid, its importance gradually decreased after the occupation of city by the local dynasties. Both the sultanate struggles in the Buyids period and the esoteric activities that emerged during the Saldjukids period laid the groundwork for the destruction of Arradjan. In addition to this, natural disasters such as epidemics, earthquakes and drought are among the reasons that accelerate the collapse of city. For this reason, the reasons for the disappearance of Arradjan were examined in two parts, political and human. In this study, the process from the conquest of city by Muslims to its destruction will be tried to be revealed by making use of the main sources and modern research works of the period.